Huntington disease reduced penetrance alleles occur at high frequency in the general population. (19th July 2016) - Kay, Chris; Collins, Jennifer A.; Miedzybrodzka, Zosia; Madore, Steven J.; Gordon, Erynn S.; Gerry, Norman; Davidson, Mark; Slama, Ramy A.; Hayden, Michael R.
Abstract : Objective: To directly estimate the frequency and penetrance of CAG repeat alleles associated with Huntington disease (HD) in the general population. Methods: CAG repeat length was evaluated in 7, 315 individuals from 3 population-based cohorts from British Columbia, the United States, and Scotland. The frequency of ≥36 CAG alleles was assessed out of a total of 14, 630 alleles. The general population frequency of reduced penetrance alleles (36–39 CAG) was compared to the prevalence of patients with HD with genetically confirmed 36–39 CAG from a multisource clinical ascertainment in British Columbia, Canada. The penetrance of 36–38 CAG repeat alleles for HD was estimated for individuals ≥65 years of age and compared against previously reported clinical penetrance estimates. Results: A total of 18 of 7, 315 individuals had ≥36 CAG, revealing that approximately 1 in 400 individuals from the general population have an expanded CAG repeat associated with HD (0.246%). Individuals with CAG 36–37 genotypes are the most common (36, 0.096%; 37, 0.082%; 38, 0.027%; 39, 0.000%; ≥40, 0.041%). General population CAG 36–38 penetrance rates are lower than penetrance rates extrapolated from clinical cohorts. Conclusion: HD alleles with a CAG repeat length of 36–38 occur at high frequency in the general population. The infrequent diagnosis of HD at this CAG length is likely due to low penetrance. Another important contributing factor may be reduced ascertainment of HD in those of older age.